2007
DOI: 10.1590/s0104-66322007000300008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vibration on bed voidage behaviors in fluidized beds with large particles

Abstract: -The effects of vibration parameters, operating conditions and material properties on bed voidage were investigated using an optical fiber probe approach in a vibrating fluidized bed with a diameter of 148 mm. Variables studied included frequency (0-282 s -1 ), amplitude (0 mm-1 mm), bed height (0.1 m-0.4 m) as well as four kinds of particles (belonging to Geldart's B and D groups). The axial and radial voidage distribution with vibration is compared with that without vibration, which shows vibration can aid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Mechanical vibration has been widely utilized in fluidization of coarse particles, , drying , and spray coating , likely due to its ability to overcome cohesive forces such as the van der Waals force and liquid bridge force. Our previous study demonstrated that mechanical vibration to a pulsed fluidized bed was only beneficial when standalone gas pulsation was insufficient in breaking up the cohesive forces between particles, especially for particles with high moisture content .…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical vibration has been widely utilized in fluidization of coarse particles, , drying , and spray coating , likely due to its ability to overcome cohesive forces such as the van der Waals force and liquid bridge force. Our previous study demonstrated that mechanical vibration to a pulsed fluidized bed was only beneficial when standalone gas pulsation was insufficient in breaking up the cohesive forces between particles, especially for particles with high moisture content .…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that gas-vibro-fluidization usually has higher circulation velocities compared to conventional gas-fluidization [11]. The vertical oscillations overlaying the vibration layer shows that vibration can help fluidize particles, and the axial and radial distribution of holes in a layer with vibration is more uniform than without it [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The type of dryer used is based on the need and the desired properties of drying products. Some of the new systems like desiccant [41], electro hydrodynamic and hybrid dryers [29], vibrated fluidized bed [19]& [48], fluidized bed [37]& [43], freeze [2]& [34], hot air drying [9], infrared [13,14], [16], intermittent [11], microwave [21], [49] & [53],and vacuum [44] have been utilized and investigated by researchers for drying the food products.…”
Section: Classification Of Drying Systemsmentioning
confidence: 99%
“…3. Dening Jia et al [8] investigated the effect of various parameters on the drying performance of pulsed fluidized vibrated bed of biomass particles and suggested high temperature and gas flow rate for better drying.Fagunwa et al [11] developed an intermittent solar dryer for Cocoa Beans and reported that drying performance is efficient than the traditional method.Jin et al [19] studied the effect of vibration parameters of a vibrated fluid bed dryer using an optical fiber probe approach and proposed an empirical correlation to predict bed voidage.Kejing An et al [23] studied the drying characteristics of ginger rhizome using five different drying process such as hot air drying, freeze drying, infrared drying, microwave drying (MD) and intermittent microwave and convective drying(IM&CD) and found that MD and CD method is good in preserving thermo sensitive materials with less power Liliana Seremet et al [26] investigated the drying characteristics of pumpkin using hot air drying and combined drying process and concluded that the rehydration capacity of hot air drying is higher.Magdalena Zielinska and Anna Michalska [27] evaluated the drying characteristics of blueberries and found that effect of combined hot air convective drying at 90°C and microwave vacuum drying process produces better results in drying time and quality than these processes have been carried out separately. Nadine Sangster et al [32] developed a prototype for an automated cocoa drying house which is s equipped with automated roof which is automatically opened during sunlight and closed if sunlight is not there and fermenter, automatic heaters and a remote control feature for the automated components.…”
Section: Analysis Of Effectiveness Of Drying Systemsmentioning
confidence: 99%